Predicting movement of stock of "Y" using Sutte Indicator - Ansari Saleh Ahmar; Abdul Rahman; Andi Nurani Mangkawani Arifin; Alfatih Abqary Ahmar (Cogent Economics & Finance, 2017)
The aim of this study is to apply technical analysis Sutte Indicator at stock market that will assist in the decision-making process in investment to buy or sell stocks. This study took data from Stock of 'Y' which listed in the NasdaqGS from the period 18 May 2012 to 30 August 2016. The performance of the Sutte Indicator can be checked with comparison with Moving Average Convergence/Divergence and Simple Moving Average. For comparison of the reliability of prediction, we can use the mean absolute percentage error, mean absolute deviation, and mean of square error.
Keywords: 330; predicting of stock; stock market; Sutte Indicator; technical analysis